Optimizing Civic Education Learning Motivation in Fifth Grade Elementary School through a Best practice Learning Model-Based Approach - Rif’an Romdloni Fatahudin (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to enhance the learning motivation of fifth-grade students at Public Alementary School (SDN) Bandunghrajo 2 in Civic Education (PPKn) through an approach based on the best practice learning model, employing the Classroom Action Research (CAR) method. Involving 30 students, the study gathered data through observation, interviews, and motivation tests. The implementation of the best practice learning model, incorporating interactive strategies, technology, and relevant content integration, successfully created a motivating learning environment. Results indicated a significant improvement in PPKn learning motivation throughout the CAR cycles. The research contributes to understanding the effectiveness of this approach at the Elementary School level. Practical implications provide guidance for teachers and policymakers in designing motivating learning strategies for students to actively engage in understanding the values of Pancasila and citizenship. The findings support efforts to enhance the quality of moral and citizenship education at the elementary level.